USE OF WASTEWATER IN THE PRODUCTION OF AROEIRA SEEDLINGS - RAIMUNDO FERNANDES DE BRITO (Revista Caatinga, 2018)
The use of wastewater has emerged as alternative to control environmental pollution and a viable option to improved water availability in the arid and semiarid zones. In this study, the effects of irrigation solution with domestic sewage effluent and, of growing substrate on growth of Aroeira seedlings was examined in a greenhouse experiment. The effects of five irrigation solution (Public-supply water, PSW, domestic sewage effluent, DSE and the mixtures of 75% DSE + 25% PSW, 50% DSE + 50% PSW and 25% DSE + 75% PSW) and two growing substrate (75% soil + 25% bovine manure and, 75% soil + 25% coconut fiber) were used in a completely randomized block design, arranged as split plots with three replications for each treatment. The evaluations were made at 30, 60, 90 and 150 days after planting, and the parameters following were measured: stem diameter, shoot height, relationship between height and diameter, shoot/root dry matter ratio, dry matter of the root, shoot and total and, Dickson index. The analysis results indicated that the irrigation solution composed by raw sewage effluent or mixed with Public-supply water increased the growth and improved morphological index of Aroeira seedlings, being the better development found when plant of Aroeira were grown in bovine manure + soil substrate under irrigation with solution containing 100% domestic sewage effluent.